PENGARUH STRUKTUR KEPEMILIKAN MANAJERIAL DAN PUBLIK, UKURAN PERUSAHAAN, EBIT/SALES DAN TOTAL DEBT/TOTAL ASSETS TERHADAP NILAI PERUSAHAAN YANG TELAH GO PUBLIC DAN TERCATAT DI BURSA EFEK JAKARTA - Budi, Soepriyanto; Titiek, Suwarti (Jurnal Ilmiah Telaah Manajemen, 2004)
Companies listed in stock exchange have a different ownership structure with ordinary companies. Baicaally, the main differences are that they have public stockholders beside managerial stock holders. There have suggested that there werw are relationship between ownership composition and firm value. Various researches had been conducted in this area with companies listed developed capital market as an object. So this is a motivation to do this research in emerging capital market mainly in Indonesia capital market. This research aimed to scrutinize the impact of managerial ownership firm’s size, EBIT/sales and total debt/total asset on firm’s value which proxies with price book value. Indonesia Capital Market Directory and BEJ corner provided data needed, while 72 companies were obtaid ed by using purposive sampling method as a sample in this study. Research question will be answer by using multiple regression metho technique. The findings shows that according partial mahnagerial ownership firm’s size EBIT/sales and total debt/total assets variable have significant value of 0.02; 0.02; 0.00 and 0.00, because significant value are under 5% so it will have significant impact on firm’s value. Public ownership haven’t significant impact on firm’s value, bcause significant value upper 5% that are 0.21%. in simultan way all independent variables are free to signicantly impact an firms value, because significant value is under 5% that is 0.00. coefisient determinant analysis is 37% so that variation independent variables can explained firm’s value in 37% and 63% explained uther factor outside model. Key words: managerial ownership, public ownership, firm’s size, EBIT/sales, total debt/total assets and value companies.